2010
DOI: 10.1586/eci.09.73
|View full text |Cite
|
Sign up to set email alerts
|

Management of anaphylaxis in the emergency setting

Abstract: Anaphylaxis is a life-threatening emergency that appears to be increasing in frequency. It affects males and females of all ages and ethnic groups. The most common triggers include foods, drugs and venom from stinging insects, although any of a number of other triggers may also be implicated. Death, when it occurs, tends to be due to respiratory and/or cardiovascular compromise, but most of these fatalities can be prevented by appropriate avoidance measures and emergency management. The management of anaphylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Delayed administration of epinephrine is a risk factor for severe and biphasic reactions and a fatal outcome [10,98,157,163,172]. A clinician should not wait for overt signs of distributive shock or cardiovascular compromise to administer epinephrine [173][174][175][176][177][178][179]. Due to the fact that patients who have fatal anaphylaxis tend to have a delay in epinephrine administration from the time of allergen exposure, it is recommended that epinephrine be given as soon as possible [16].…”
Section: Treatmentmentioning
confidence: 99%
“…Delayed administration of epinephrine is a risk factor for severe and biphasic reactions and a fatal outcome [10,98,157,163,172]. A clinician should not wait for overt signs of distributive shock or cardiovascular compromise to administer epinephrine [173][174][175][176][177][178][179]. Due to the fact that patients who have fatal anaphylaxis tend to have a delay in epinephrine administration from the time of allergen exposure, it is recommended that epinephrine be given as soon as possible [16].…”
Section: Treatmentmentioning
confidence: 99%
“…Based on modeling studies that provide estimates of the magnitude of effect that is very unlikely to be explained by bias [39,40], the GRADE system defines a large effect as a RR of more than 2.0 or less than 0.5 (based on consistent evidence from at least two studies, with no plausible confounders) and a very large effect as a RR of more than 5.0 or less than 0.2 (based on direct evidence with no major threats to validity). For example, the extremely large and consistent effect [41] of epinephrine injections in anaphylactic shock leaves us convinced of the benefits of the intervention. Moreover, the GRADE approach can be particularly useful applied in cases in which carrying out RCTs is impossible.…”
Section: Large Magnitude Of Effectmentioning
confidence: 99%
“…It is in this respect important to appreciate that, whilst all food allergies have the potential to induce anaphylaxis, some foods are more likely than others to cause potentially lifethreatening reactions. 3 Among anaphylactic reactions attributed to foods, 23-47% are triggered by peanut protein. 4 It has been suggested that ingestion of peanuts by mothers during pregnancy or while lactating could be a potential risk factor for the development of peanut allergy, but the evidence for this is weak.…”
Section: Introductionmentioning
confidence: 99%